Implementasi Metode Double Moving Average dan Regresi Linier untuk Peramalan Asam Sulfat di PT.XYZ - Debi Yulian; Ade Momon (Jurnal Serambi Engineering, 2023)
AbstractPT. XYZ is an excellent stockist and supplier of commodities for many enterprises that need chemicals. The way that companies can survive and businesses can rotate also increases, requiring appropriate policies to increase productivity and optimize in managing the company starting from the incoming activities, processes and results achieved. Forecasting is an important thing to do when it will produce an item or product. In this study, we used past data on sulfuric acid product demand from February 2021 to January 2022. The purpose of this study is to estimate the amount of demand in the coming period in order to meet consumer demand. Double moving averages and linear regression were used as methods in this study, followed by determining the lowest MSE and MAPE values used to forecast sulfuric acid demand at PT. XYZ. The lowest MSE and MAPE values were generated using linear regression methods with MSE values of 2.724 and MAPE of 2.173 for PT. A. At PT. B obtained MSE 2.397 and MAPE 1.324. The value is lower than MSE and MAPE double moving average. For this calculation, the linear regression method can be used as a forecasting method in this calculation.Keywords: forecasting, double moving average, time series, linear regression, mean absolute percentage error